210Pb-Derived Bioturbation Rates in Sediments Around Seamounts in the Tropical Northwest Pacific - Lin, Feng; Lin, Cai; Lin, Hui; Sun, Xiuwu; Lin, Li (Frontiers in Marine Science, 2021)
To evaluate bioturbation coefficients (DB) and mixing depths (L), 210Pb and 226Ra activity was measured in two sediments cores (from water depths of 5,398 m and 4,428 m), which were collected from seamount areas in the Northwest Pacific. Using a steady-state diffusion mode, we estimated DB values of 16.8 and 24.1 cm2/a, higher than those in abyssal sediments and those predicted by traditional empirical equations. Corresponding L values varied between 19.3 and 23.1 cm. These high values indicate that seamounts are the area of active bioturbation. A one-dimensional model for the transport of total organic carbon (TOC) from the surface layer of sediments to the deep layer was developed using the distribution pattern of the specific activity of excess 210Pb (210Pbex) and its relationship with TOC. The model showed that the TOC flux transmitted downward by bioturbation was 0.09 mmol/(cm2⋅a) and 0.12 mmol/(cm2⋅a).